Structural information and communication complexity : 27th International Colloquium, SIROCCO 2020, Paderborn, Germany, June 29-July 1, 2020, proceedings /: 27th International Colloquium, SIROCCO 2020, Paderborn, Germany, June 29-July 1, 2020, proceedings. (2020) - Unknown
No abstract available